Ecologia das assembleias de peixes do Parque Estadual de Jurupará (PEJU,SP) - Teshima, Fernanda Ayumi (2013)
The general aim of this thesis is to understand the fish assemblages of headwater and small streams of Jurupará State Park, a protected area located in São Paulo State. Located among other four protected areas, the park functions as a connector and contributes to the conservation of the Atlantic Forest and Upper Juquiá River basin, located in the Ribeira de Iguape River basin. Ten stream reaches (3rd to 5th order) were sampled between June and December 2010. Ichthyofauna was collected with electrofishing equipment, while environmental variables were visually quantified during onsite surveys and with cartographic maps of the region. Local environmental variables consisted of coarse substrate, diversity of water velocity, proportion of mesohabitats (i.e., riffles, pools and runs), banks stability and shading. Regional environmental variables consisted of vegetation cover, catchment area, altitude and stream reach position according to sub-basin. Fish assemblages structure analyses according to environmental variables were divided into two chapters, presented as scientific papers. The first chapter analyzed two issues, (i) fish assemblages α and β components and (ii) patterns in species composition according to environmental variables. In order to approach the first issue, we used multiplicative partitioning of true diversities to calculate α and β components and compare them with expected values in a null model. The second issue was approached by reducing the number of environmental variables with PCA and using the most significant gradients as predictor variables in a db-RDA, followed by a species composition variation partitioning according to each significant variable. The α and β components observed were different from expected by chance and the variation in species composition was strongly related to environmental variables operating at different scales. The proportion of coarse substrate and bank stability contributed with 6% of species composition variation, while sub-basin contributed with 10%. Possibly, the low percentage of variation explained by the model can be justified by the scale of the environmental variables. If the structuring of fish assemblages follows the null metacommunity model predictions, then variables related to stream topology and species intrinsic characteristics are more likely to better explain the spatial organization of the fauna. In Chapter II, we used data of occurrence frequency, average abundance and biomass to identify rare and common species of the fish assemblages. Withal, we used linear multiple regression models to analyze the abundance of Isbrueckerichthys epakmos according to local environmental variables. The importance of this species relies on its classification as endemic in Ribeira de Iguape River basin and threatened, according to IUCN criterion. Five species were very abundant and widely distributed in the sampled reaches, including I. epakmos, whose distribution was strongly related to coarse substrate and proportion of riffles and runs. Eight rare species were identified, two of them being also endemic of Ribeira de Iguape River basin, Astyanax ribeirae e Neoplecostomus ribeirensis. The elevated taxonomic and functional diversity observed indicates that the studied streams still hold physical integrity to support the biota and, probably, local ecological processes, despite the presence of impoundments that support four small dams installed inside the park.